Prevalence of prenatal brain abnormalities in fetuses with congenital heart disease: a systematic review. (September 2016) - Khalil, A.; Bennet, S.; Thilaganathan, B.; Paladini, D.; Griffiths, P.; Carvalho, J. S.
ABSTRACT: Objectives: Studies have shown an association between congenital heart defects (CHDs) and postnatal brain abnormalities and neurodevelopmental delay. Recent evidence suggests that some of these brain abnormalities are present before birth. The primary aim of this study was to perform a systematic review to quantify the prevalence of prenatal brain abnormalities in fetuses with CHDs. Methods: MEDLINE, EMBASE and The Cochrane Library were searched electronically. Reference lists within each article were hand‐searched for additional reports. The outcomes observed included structural brain abnormalities (on magnetic resonance imaging (MRI)) and changes in brain volume (on MRI, three‐dimensional (3D) volumetric MRI, 3D ultrasound and phase‐contrast MRI), brain metabolism or maturation (on magnetic resonance spectroscopy and phase‐contrast MRI) and brain blood flow (on Doppler ultrasound, phase‐contrast MRI and 3D power Doppler ultrasound) in fetuses with CHDs. Cohort and case–control studies were included and cases of chromosomal or genetic abnormalities, case reports and editorials were excluded. Proportion meta‐analysis was used for analysis. Between‐study heterogeneity was assessed using the I 2 test. Results: The search yielded 1943 citations, and 20 studies ( n  = 1175 cases) were included in the review. Three studies reported data on structural brain abnormalities, while data on altered brain volume, metabolism and blood flow were reported in seven, three and 14 studies, respectively. The three studies (221 cases) reporting on structural brain abnormalities were suitable for inclusion in a meta‐analysis. The prevalence of prenatal structural brain abnormalities in fetuses with CHD was 28% (95% CI, 18–40%), with a similar prevalence (25% (95% CI, 14–39%)) when tetralogy of Fallot was considered alone. These abnormalities included ventriculomegaly (most common), agenesis of the corpus callosum, ventricular bleeding, increased extra‐axial space, vermian hypoplasia, white‐matter abnormalities and delayed brain development. Fetuses with CHD were more likely than those without CHD to have reduced brain volume, delay in brain maturation and altered brain circulation, most commonly in the form of reduced middle cerebral artery pulsatility index and cerebroplacental ratio. These changes were usually evident in the third trimester, but some studies reported them from as early as the second trimester. Conclusion: In the absence of known major aneuploidy or genetic syndromes, fetuses with CHD are at increased risk of brain abnormalities, which are discernible prenatally. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations.